Five new species of the genus Phlugiolopsis Zeuner, 1940 (Tettigoniidae: Meconematinae) from China - Zheng, Mengjia; Su, Jie; Shi, Fuming (European Journal of Taxonomy, 2024)
This paper reports five new species of Phlugiolopsis Zeuner, 1940 from Sichuan, Yunnan and Guangxi in China, i.e., Phlugiolopsis luojishanensis sp. nov., Phlugiolopsis lata sp. nov., Phlugiolopsis rongshuiensis sp. nov., Phlugiolopsis acuta sp. nov. and Phlugiolopsis daweishanensis sp. nov. We present a redescription of the male of Phlugiolopsis punctata Wang, Li & Liu, 2012, describe the female of Phlugiolopsis punctata Wang, Li & Liu, 2012 and the male of Phlugiolopsis pentagonis Bian, Shi & Chang, 2013 for the first time. In addition, images illustrating the morphology of these species and seven previously described species are provided. The distribution map of the genus Phlugiolopsis from China is also provided.